Pengembangan Media Pembelajaran Flashcard Berbasis Augmented Reality dalam Meningkatkan Kemampuan Hasil Belajar Peserta Didik pada Materi Pancasila dalam Diriku pada Peserta Didik Kelas IV SD Negeri Podorejo 03 - Isya'i, Abi Hikmatul; Bektiningsih, Kurniana (FONDATIA, 2025)
This study aims to develop augmented reality-based Flashcard learning media as an effort to improve the learning outcomes of fourth-grade students at SD Negeri Podorejo 03 in the subject of Pancasila Education. The research method used is Research and Development (R&D), following the ADDIE model applied across all research stages. Data collection techniques include tests and non-test methods, where the test technique involves pretest and posttest results, while the non-test methods consist of interviews, questionnaires, and documentation as supporting data. Qualitative and quantitative data analysis techniques were employed. The research subjects comprised 10 fourth-grade students for the small group trial and 20 fourth-grade students for the large group trial. The results of testing the augmented reality-based Flashcard learning media demonstrated its feasibility, as validated by media experts (93%) and material experts (88%), both classified as highly feasible. The effectiveness of this learning media is evidenced by improved student learning outcomes, as reflected in the pretest and posttest scores. In the small group trial, the scores increased from 64.9 to 79.2, with an N-gain score of 40%, categorized as moderate. Similarly, in the large group trial, the pretest and posttest scores improved from 63.9 to 79.1, with an N-gain score of 40%, also categorized as moderate. Therefore, the augmented reality-based Flashcard learning media has been proven effective in improving the learning outcomes of fourth-grade students at SD Negeri Podorejo 03 in the subject of Pancasila Education.